The Role of Health Promotion Hospital in Fulfilling Patient and Family Right in RA. Basoeni Hospital, Mojokerto - Manfaati, Rizka Lina; Soedirham, Oedojo; Triyoga, Rika S; Bastian, Ardi (Health Notions, 2018)
-